2010
DOI: 10.1111/j.1472-765x.2010.02860.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sampling procedures for DNA-based diagnosis of wood decay fungi in standing trees

Abstract: Aims:  To develop fast and reliable sampling procedures for DNA‐based diagnosis of wood decay fungi in standing trees. Methods and Results:  A total of 250 trees were tested for the presence of a suite of wood decay fungi by collecting wood frass obtained by drilling each tree once with a 4‐mm‐diameter, 43‐cm‐long bit. We identified at least one of 11 target wood decay fungi in 56 trees through multiplex PCR assays. The presence of target wood decay taxa was further investigated in these 56 trees, by analysing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 16 publications
1
40
0
1
Order By: Relevance
“…In our collection, some more rarely occurring species like Hypsizygus ulmarius have also been identified. Kretzschmaria deusta is present as an ascomycete, which was also isolated by Guglielmo et al (2010). Our isolation technique had proven to be accurate in several investigations on the occurrence of fungi and bacteria in tree interiors (Schmidt 1985;Schmidt et al 2008).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In our collection, some more rarely occurring species like Hypsizygus ulmarius have also been identified. Kretzschmaria deusta is present as an ascomycete, which was also isolated by Guglielmo et al (2010). Our isolation technique had proven to be accurate in several investigations on the occurrence of fungi and bacteria in tree interiors (Schmidt 1985;Schmidt et al 2008).…”
Section: Resultsmentioning
confidence: 93%
“…Guiglielmo et al (2007) listed many basidiomycetes from a broad range of host trees from urban and forest habitats in the Chech Republic, France, Italy, Switzerland, UK, and USA. An investigation in Italy (Guglielmo et al 2010) revealed four Ganoderma species, Perenniporia fraxinea, Laetiporus sulphureus, and fungi belonging to the genera Armillaria, Fomitoporia, Hericium, Inocutis, Inonotus s.s., Phellinus s.s., Pleurotus, Pseudoinonotus, Schizophyllum, Stereum, and Trametes. Terho et al (2007) differentiated the similar fruit bodies of Ganoderma species by ITS sequencing.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations